Emerging Risks in Food: Probiotic Enterococci Pose a Threat to Public Health through the Food Chain - Wenjiao Xu; Yuwen Fang; Qiao Hu; Kui Zhu (Foods, 2021)
Probiotics have been associated with clinical infections, toxicity, and antimicrobial resistance transfer, raising public concerns. Probiotic enterococci are emerging food risks as opportunistic pathogens, yet little attention has been paid to them. Herein, we collected 88 enterococcal isolates from probiotic products used for humans, companion animals, livestock, and aquaculture. Results showed that all 88 probiotic enterococcal isolates harbored diverse virulence genes, multiple antimicrobial resistance genes, and mobile genetic elements. Notably, 77 isolates were highly resistant to gentamicin. Representative enterococcal isolates exerted toxic activities in both in vitro and in vivo models. Collectively, our findings suggest that probiotic enterococci may be harmful to hosts and pose a potential threat to public health.